Development and testing of hybrid precast steel-reinforced concrete column-to- H shape steel beam connections under cyclic loading. (15th May 2020) - Wu, Chenglong; Yu, Sujian; Liu, Jiming; Chen, Genda
Highlights: A new type of modular composite joint is proposed. Physical tests and finite element analysis of composite joints are carried out. Verify the correctness of modular composite joint finite element model. Proposed calculation formulas can describe joint strength under cyclic load. Modular composite joint meet the requirements of 'strong column weak beam'. Abstract: This paper proposes a steel-reinforced concrete column-steel beam composite joint (MPCJ) suitable for modular prefabricated building construction and investigates its seismic performance. The proposed MPCJ has simple structure, convenient construction, and good bearing capacity. This study performs an experimental investigation in which three MPCJ specimens with different beam-column connections (bolted connection, welded connection, and bolted-welded hybrid connection) are subjected to low-cycle reversed loading and are investigated for the elastic and elastoplastic development trends, failure characteristics, and seismic response. Each specimen undergoes bending failure at the end of the beam that follows the buckling of the flange connecting plate. MPCJs exhibit stable hysteretic curves, reasonable strength and stiffness degradation, as well as good ductility and energy dissipation performance. The ductility coefficients and the equivalent viscous damping coefficients of MPCJ specimens are within the seismic performance limits prescribed by structural design standards. The joint rotation of an MPCJ caused by shear deformation appears different from that of conventional beam-column joints. Finite element models of MPCJ specimens are established by ABAQUS, and the finite element results are compared with the experimental results, thus verifying the feasibility and accuracy of the finite element models. Based on the experimental findings and the numerical validation, simplified equations are proposed for calculating the flexural and shear bearing capacity of an MPCJ. The proposed MPCJ connection will be useful in the modular construction of concrete-steel composite frame structures.